Educational Values in Modern Javanese Poetry: A Philosophical Study Based on the Thoughts of Ki Hajar Dewantara - Haryanti; Darni; Resdianto Permata Raharjo; Anas Ahmadi (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
Poetry, as a form of literary expression, not only offers aesthetic beauty through the arrangement of words but also contains profound meanings that represent values of life, culture, and education. In the context of modern Javanese literature, poetry serves as a reflective medium of the collective experiences of Javanese society amidst dynamic change. Modern Javanese poetry acts as a bridge between traditional heritage and modern awareness, combining artistic expression with moral messages.This study aims to examine the educational values embedded in modern Javanese poetry through the lens of Ki Hajar Dewantara’s educational philosophy. His seven fundamental principles—freedom, nature, culture, humanity, nationality, kinship, and student-centered education—serve as the theoretical framework for analysis. Through a literature review and hermeneutic approach, this research reveals that modern Javanese poetry holds transformative educational messages relevant to character development and cultural preservation.